2019
DOI: 10.1016/j.dib.2019.103804
|View full text |Cite
|
Sign up to set email alerts
|

Data on agricultural and nonagricultural land use in peri-urban and rural area

Abstract: The data in this article describes the land use characteristics at peri-urban and rural areas, on Jember District, in the Province of East Java, Indonesia. The types of land use covered in the data are agricultural and residential land. The data was a result of a research collaboration between the Department of Agribusiness, Department of Soil Science, and the Department of Agricultural Extension in the University of Jember. The general purpose of the data collection was to compare the characteristics of diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 1 publication
2
4
0
Order By: Relevance
“…The fertilizer variable demonstrated that the application of chemical fertilizer decreases the degree of P-I. In line with the previous discussion, farmers often apply more agrochemicals to retain their crop 1 The example of data on extensive use of agrochemical in Indonesian farming can be found here [93]. production.…”
Section: Technical Factorssupporting
confidence: 69%
“…The fertilizer variable demonstrated that the application of chemical fertilizer decreases the degree of P-I. In line with the previous discussion, farmers often apply more agrochemicals to retain their crop 1 The example of data on extensive use of agrochemical in Indonesian farming can be found here [93]. production.…”
Section: Technical Factorssupporting
confidence: 69%
“…The fertilizer variable demonstrated that the application of chemical fertilizer decreases the degree of P-I. In line with the previous discussion, farmers often apply more agrochemicals to retain their crop 1 The example of data on extensive use of agrochemical in Indonesian farming can be found here [93].…”
Section: Technical Factorssupporting
confidence: 72%
“…We gathered the first data through enumeration to all WUAs chairman in KWID. This process is similar to the enumeration process in our previous data article [2] . The purpose of this enumeration is to define the location of each WUA and its corresponding operation area.…”
Section: Experimental Design Materials and Methodsmentioning
confidence: 56%